Cover Picture: Distinctive Potential Behavior at the Oxidized Surface of a Semiconductor Device in a Concentrated Aqueous Salt Solution (ChemElectroChem 9/2014). Issue 9 (4th September 2014) - Maekawa, Yuki; Shibuta, Yasushi; Sakata, Toshiya
<x xml:space="preserve">Abstract</x> Concentrate on the potential! The unique potential behavior of a semiconductor‐based ion sensor in concentrated aqueous NaCl solutions was found experimentally by using an on silico technique. These results were supported by in silico simulations, which enabled the identification of specific interfacial properties resulting from the spatial separation of ions and the hydration of ions, and the continuous shift of the potential profile based on ionic charges near the interface. (DOI: 10.1002/celc.201402069).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>